Ionic Liquids in Pharmaceutical and Biomedical Applications: A Review - Yue Zhuo; He-Li Cheng; Yong-Gang Zhao; Hai-Rong Cui (MDPI AG, 2024)
The unique properties of ionic liquids (ILs), such as structural tunability, good solubility, chemical/thermal stability, favorable biocompatibility, and simplicity of preparation, have led to a wide range of applications in the pharmaceutical and biomedical fields. ILs can not only speed up the chemical reaction process, improve the yield, and reduce environmental pollution but also improve many problems in the field of medicine, such as the poor drug solubility, product crystal instability, poor biological activity, and low drug delivery efficiency. This paper presents a systematic and concise analysis of the recent advancements and further applications of ILs in the pharmaceutical field from the aspects of drug synthesis, drug analysis, drug solubilization, and drug crystal engineering. Additionally, it explores the biomedical field, covering aspects such as drug carriers, stabilization of proteins, antimicrobials, and bioactive ionic liquids.